Cadaveric kidney transplantation in an ESRD patient with Klippel–Feil syndrome—A case report. Issue 1 (19th January 2023) - Dialameh, Hossein; Namdari, Farshad; Etezadi, Farhad; Inanloo, Seyed Hassan; Mousavi, Seyed Hamid; Rahimzadeh, Hormat; Nazarpour, Mohammad Javad
Abstract: Klippel–Feil syndrome (KFS) is a congenital skeletal disorder with classic clinical triad consisting of short neck, low hairline, and limitation of neck movement. In addition to skeletal deformities, diagnosed cases of KFS may have other anomalies such as cardiac, neurologic, and genitourinary disorder. We report a case of KFS with associated anomalies such as short neck, limitation of neck movement, scoliosis of cervical spine, and dextrocardia who received successful cadaveric kidney transplantation. This article aims to present kidney transplantation as option of treatment in KFS patient with ESRD and emphasize on the difficulty in airway management of this patient. Abstract : Klippel–Feil syndrome is a skeletal disease with fusion of cervical vertebrae. During surgery, attention should be paid to the difficulty in airway management and the importance of being prepared for it using video laryngoscopy. Because anatomy of vessel and bladder were normal, technique of kidney transplant surgery was routine.